Genetic diversity among perennial wild rice Oryza rufipogon Griff., in the Mekong Delta. Issue 5 (19th February 2019) - Lam, Dinh T.; Buu, Bui C.; Lang, Nguyen T.; Toriyama, Kinya; Nakamura, Ikuo; Ishikawa, Ryuji
Abstract: Oryza rufipogon Griff. is a perennial species of wild rice widely distributed along the channels and rivers of the Mekong Delta, Vietnam. This study attempted to find centers of diversity among wild rice populations in this area and their inter‐relationships. The highest genetic diversity was found in the Dong Thap population and the lowest in the Can Tho population. Maternal diversity evaluated using chloroplast INDELs detected ten plastid types, five of which were novel relative to other Asian countries. The mitochondrial genome suggested two unique deletions. One 699‐bp deletion via short tandem repeats was accompanied by another deletion including orf153 . All accessions carrying the mitochondrial type were found in a particular plastid type. This unique maternal lineage was confined to specific channels where it showed vigorous vegetative growth in comparison to upstream areas where various maternal lineages and maximum genetic diversity occurred. This area along the Mekong Delta is a center of not only nuclear but also maternal diversity. Abstract : Perennial wild rice inhabited in Can Tho, Vietnam, propagating vegetatively.